Sociální ekonomika v ČR a její řešení v projektu Hefaistos - Leznar, Zdeněk (Univerzita Pardubice, 2007)
Between the people and regions they inhabit an unequality of chances originates since the very beginning. It did not prove successful to eliminate this unequality in the course of history and at present we meet with it also in existing market economy based on free business for the purpose of profit acquirement. Particularly unemployed people, new school graduates without previous practice, people with insufficient education, people in pre-pension age, people without convenient housing , poor people and mothers with small children are exposed to those social inequalities. Furthermore also persons who have found themselves - for various reasons – out of the main society stream and have lost adequate living background, especially housing and employment, and subsequently financial income as well. A specific group consists of people with health problems, healthwise or otherwise handicapped people, people dependent on drugs, homeless people, people after return from sentence, from mental homes, after return from a long-term illness, and others. A modern group consists of immigrants and refugees, particularly without professional and language knowledge, and ethnical minorities. This problem is so much important that even European Union tries to solve it. A fundamental objective is seen in achievement of maximum employment. The European Commission in ensuring this commitment recommends to take aim at the sphere of social economy, above all at activities connected with providing payed as well as unpayed services, at repeated introduction of disadvantaged groups of citizens into working process and at creation of equal conditions between groups of citizens, including among men and women. Social economy in European Union countries comprises round 900,000 enterprises and represents about ten per cent of gross domestic product (GDP) and employment. Social economy is a part of a social and economic model of the future European Union. The European Union enforces a principle of solidarity and differences both between different groups of citizens and between different regions. EU leans upon social economy enterprises which are already well introduced in the given locality and follow necessary relations with local authorities, and enterprises that set themselves an aim to prevent exclusion of some persons from domain of common society, and which on the contrary follow their introduction into this society. Within the European Union countries it has been striven for social enforcement of these people by different means, among which an important role is played by the so-called social economy. Social economy belongs as yet in our country among conceptions which only very hardly penetrace into current life, namely also on the level of terminology/conceptuality. Therefore it is desirable that possibilities, methods and conditions for their return should be found , i.e. to establish social inclusion and restrict social exclusion as much as possible. This has been the main reason of origination of HEFAISTOS Development Partnership.
Keywords: social economy; social exclusion; social inclusion; social enterprise; social establishment